2015
DOI: 10.2807/1560-7917.es2015.20.16.21101
|View full text |Cite|
|
Sign up to set email alerts
|

Changing hepatitis A epidemiology in the European Union: new challenges and opportunities

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 24 publications
2
56
0
2
Order By: Relevance
“…Also, the use of anti-HAV-IgG immunoenzymatic assay in the previous study and anti IgM kits in this study might have contributed to the difference in the two results. The result of this study is also similar to the trend reported among food handlers in Khartoum locality, Sudan (4.40%) and 37.25% in central Karnataka, India with same category of endemicity but varying prevalence rates [7,22,26]. This similarity could be attributed to the general downward trend in the global seroprevalence of HAV infections in most countries of the world.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Also, the use of anti-HAV-IgG immunoenzymatic assay in the previous study and anti IgM kits in this study might have contributed to the difference in the two results. The result of this study is also similar to the trend reported among food handlers in Khartoum locality, Sudan (4.40%) and 37.25% in central Karnataka, India with same category of endemicity but varying prevalence rates [7,22,26]. This similarity could be attributed to the general downward trend in the global seroprevalence of HAV infections in most countries of the world.…”
Section: Discussionsupporting
confidence: 78%
“…The 0.67% prevalence rate obtained in this study is classified as hypoendemicity. The HAV endemicity rates were defined as: Low = ≤ 50% intermediate = 51-89%, High = ≥ 90% [22]. This revealed a similar trend dropping from a previous report of 7.2% among young adolescent and school children in Kaduna in 2013 to the present rate [2,22].…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In rare cases HAV can be transmitted via infected blood of asymptomatic donors and people in incubation period. 2 Despite the clinical form of the disease (asymptomatic, subclinical, symptomatic or fulminant), the sick person with acute infection is the reservoir for spreading of the infection. In the late incubation period (1-2 weeks before the onset of prodromal symptoms) and during the fi rst week after the onset of jaundice, the virus is released with the feces in concentrations higher than 10 8 particles in 1 ml.…”
Section: Introductionmentioning
confidence: 99%